Visualisasi Heroik Makhluk Mitologi: Analisis Ilustrasi Desain Karakter Genderuwo Penjaga Mata Air Desa Ngrundul - Fatikha Dahayuna Qaulansadida (Penerbit dan Percetakan, CV. Picmotiv, 2026)
The availability of clean water in Ngrundu, Klaten faces a decline in ecological awareness due to the water spring preservation myths. Conventional perspectives mistakenly identify Genderuwo as a destructive horror figure, thereby eroding the conservation values behind gayam trees as natural water binders. This study aims to produce a radical visual reconstruction of Genderuwo as a Water Spring Protector into a heroic figure through digital illustration. The method used is descriptive qualitative based on practice-based research. The design results manifest in a fictional character named